2018
DOI: 10.1051/matecconf/201820302004
|View full text |Cite
|
Sign up to set email alerts
|

Delays and Cost Overruns Causes During Construction of Palm Oil Refinery Projects

Abstract: Delays and cost overruns are obviously common problems in the construction industry in several developed and developing nations. The purpose of this study is to identify factors cause delays and cost overruns in the construction of palm oil refinery projects in Malaysia. A questionnaire survey of a randomly selected sample was filled by 89 respondents. The questionnaire included 179 factors which classified into 13 groups. The degree of importance of the delays and cost overrun factors were evaluated and ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…As stated by Abdullah et al (2018), delays in subcontractor's work, lack of subcontractor skill, and poor planning and scheduling were the most crucial factors causing a delay in Palm oil refinery construction projects in Malaysia. Sweis et al (2018b) reported causes of delay in Iran's oil and gas projects using root cause analysis and under five categories consisting of financial-, operational-, site-, human and equipment-and external-related.…”
Section: Causes Of Delayed Construction Projects: Oil and Gas Projectsmentioning
confidence: 99%
“…This demonstrated among many the experiences of the respondents, improving the credibility and reliability of the information provided by the respondents on the subject. The second part then investigated the awareness of PPE adaptation in infrastructure projects [20]. The third part identified and assessed the safety factors and barriers of PPE adaptation in infrastructure projects [21].…”
Section: Figure 1 Flow Chartmentioning
confidence: 99%